1979
DOI: 10.1139/z79-174
|View full text |Cite
|
Sign up to set email alerts
|

Ogmogaster antarcticus Johnston, 1931 (Trematoda: Notocotylidae) from the bowhead whale, Balaena mysticetus L., at Barrow, Alaska

Abstract: One specimen of the trematode Ogmogaster antarcticus Johnston, 1931 was recovered from a sample of bowhead whale ingesta collected at Barrow, Alaska. This represents a new host record and extends the known geographic distribution of this helminth some 5000 km by sea north of British Columbia, Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…pentalineatus Rausch &Fay, 1966) have all been found in baleen whales. O. pentalineatus has been reported only from Eschrichtius robustus, while O. antarcticus has been reported from both hemispheres and pinniped hosts, as well as the fin Balaenoptera physalus, sei B. borealis and bowhead Balaena mysticetus whales (Rausch & Fay 1966, Shults 1979. Rausch & Fay (1966) reviewed previously collected specimens of Ogmogaster and concluded that the taxonomic status of O. antarcticus should be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…pentalineatus Rausch &Fay, 1966) have all been found in baleen whales. O. pentalineatus has been reported only from Eschrichtius robustus, while O. antarcticus has been reported from both hemispheres and pinniped hosts, as well as the fin Balaenoptera physalus, sei B. borealis and bowhead Balaena mysticetus whales (Rausch & Fay 1966, Shults 1979. Rausch & Fay (1966) reviewed previously collected specimens of Ogmogaster and concluded that the taxonomic status of O. antarcticus should be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…In gray whales, rare fluke infection was associated with chronic cholangitis ( Rice and Wolman, 1971 ). Ogmogaster plicatus specimens have been isolated from ingesta of several BCB bowhead whales ( Shults, 1979 , Heckmann et al, 1987 ), but neither eggs nor adult specimens were detected during a recent retrospective fecal parasite survey ( n =159; 2002–15; Ballweber and Stimmelmayr, unpublished data). Trematodes, in low numbers, associated with mild gastroenterocolitis were observed on histopathology in an individual bowhead whale (NSB-DWM 2010WW4; unpublished data).…”
Section: Infectious Diseasesmentioning
confidence: 99%